2018
DOI: 10.2174/1381612824666180911114210
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Specificity Role of Transcription Factor FOXO in Type 2-diabetes and Cancer

Abstract: The FOXO (Forkhead box O) transcription factors are implicated in several signaling pathways and play a vital role in various cellular and physiological processes include for instance, ROS (reactive oxygen species) response, cell proliferation, regulation of programmed cell death, longevity, metabolism and cancer and regulation of cell cycle. In humans, the four FOXO family members are responsible for resemblance in their structure, regulation and functions. FOXO1 gene is highly expressed in adipose tissues an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…13 Gluconeogenesis is classically regulated by hepatocyte nuclear factor 4 a (HNF4a), 18,19 PPARa, 20 and FOXO1. 21 PT cells are the only cell type able to perform this process in the cortical kidney area, harboring the expression of rate-limiting enzymes such as fructose-1,6-bisphosphatase (FBP1), phosphoenolpyruvate carboxykinase 1 (PCK1), or glucose-6-phosphatase (G6PC) and using lactate as the main substrate. 22 Renal gluconeogenesis appears particularly relevant in acute conditions, because it is also regulated by pH and stress hormones, and provides 40% of systemic gluconeogenesis in fasting conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Gluconeogenesis is classically regulated by hepatocyte nuclear factor 4 a (HNF4a), 18,19 PPARa, 20 and FOXO1. 21 PT cells are the only cell type able to perform this process in the cortical kidney area, harboring the expression of rate-limiting enzymes such as fructose-1,6-bisphosphatase (FBP1), phosphoenolpyruvate carboxykinase 1 (PCK1), or glucose-6-phosphatase (G6PC) and using lactate as the main substrate. 22 Renal gluconeogenesis appears particularly relevant in acute conditions, because it is also regulated by pH and stress hormones, and provides 40% of systemic gluconeogenesis in fasting conditions.…”
Section: Discussionmentioning
confidence: 99%
“…, 16 , 17 Gluconeogenesis encompasses a series of enzymatic reactions that are usually regulated in opposition to glycolysis 13 . Gluconeogenesis is classically regulated by hepatocyte nuclear factor 4 α (HNF4 α ), 18 , 19 PPAR α , 20 and FOXO1 21 . PT cells are the only cell type able to perform this process in the cortical kidney area, harboring the expression of rate-limiting enzymes such as fructose-1,6-bisphosphatase (FBP1), phosphoenolpyruvate carboxykinase 1 (PCK1), or glucose-6-phosphatase (G6PC) and using lactate as the main substrate 22 …”
mentioning
confidence: 99%
“…Insulin on the other hand downregulates renal gluconeogenesis (66), which could be due to PCK1/G6Pc regulation through phosphorylation (66,67) but also to the reduction of substrates availability (glycerol and glutamine) (68,69) or their redirection to the oxidative pathways (13,68). Gluconeogenesis is regulated by factors implicated in global metabolic regulation, such as peroxisome proliferator-activated receptor alpha (PPARα) (70), Forkhead Box O1(FOXO1) (71) and hepatocyte nuclear factor 4 alpha (HNF4α) but also by glucose levels, through the modification of the NAD + /NADH ratio which causes an indirect downregulation of PCK1 at mRNA level (66). Acidosis also seems to play a role, with the induction of PCK1 at the mRNA and enzymatic activity level (72,73) and hence increased renal glucose production.…”
Section: Glucose Metabolism During Kidney Diseasementioning
confidence: 99%
“…The same results were also obtained when we tested the effect of BKM120 on the apoptotic effect of pioglitazone (Figure 4). The results of the previous studies indicated that PPARγ, as a nuclear receptor, has a tight interplay with different nuclear proteins, foremost nuclear factor (NF)‐κB and forkhead transcription factors (FOXO) (Fatima et al, 2018; Kunicka et al, 2019). In agreement with the results of Annexin‐PI staining, the qRT‐PCR analysis also revealed that in the presence of CAL‐101, pioglitazone might have more ability to increase the expression of FOXO3a and PUMA, while reducing the expression level of anti‐apoptotic genes, such as Bcl‐2, MCL‐1, and SVV (Figure 5a).…”
Section: Resultsmentioning
confidence: 99%